Managing Clinical Risk in Romania - P Radu; C Tereanu; S Baculea (Tehran University of Medical Sciences, 2008)
"nBackground: The indicators for adverse events screening, developed by Wolff in Australia, use ready available data in order to identify "red flag" cases that might need to be reviewed by clinicians in terms of medical documentation."nMethods: In this study, the 8 indicators developed by Wolff were used in the process of screening the electronic patient records from the 41 district hospitals in Romania. Data used is the Romanian Minimum Basic Data Set for 2006 collected at the National School of Public Health and Health Services Management, the institution in charge with data collection and processing. From the 8 indicators selected by Wolff, only one could not be used due to lack of data in the Romanian Minimum Basic Data Set."nResults: The distribution of these indicators in the 41 district hospitals shows wide differences among hospitals. This could represent an indication of higher clinical risk at some hospitals, but they can mean as well errors in the collection and management of data from the electronic patient records."nConclusion: The study shows that the indicators can be used by hospitals for benchmarking clinical risk, although a better standardization and monitoring of data reporting is necessary in order to increase their validity. The Minimum Basic Data Set represents an accessible instrument for identification and measuring of clinical risk, but for purpose of utilization at national level we recommend at first the validation of data used to build the indicators, followed by the testing of the sensibility, specificity, and the positive and negative predictive values.